Stabilization of sandy soil with high content of asphalt emulsion - Dantas Neto,Silvrano Adonias (2020)
Abstract The purpose of this article is to evaluate the shear strength parameters of mixtures of sandy soil with high asphalt emulsion contents for their use in geotechnical structures, such as zoned earth dams, embankments, etc. The methodology adopted consisted of: collecting and characterizing samples of sandy soil to be laboratory tested; compacting the mixtures between soils and asphalt emulsion with contents varying between 13% and 28% in weight by using different compaction methodologies; and performing direct shear tests to evaluate the parameters governing the shear strength behavior of the manufactured mixtures. Results showed that the use of a high asphalt emulsion content contributed to greater homogeneity of the mixtures. It was also found that the presence of residual asphalt gave a bilinear behavior to the sandy soil for the failure envelopes obtained from direct shear tests. At normal stresses usually less than 100 kPa, the mixtures present a cohesive intercept due the existing residual binder, while for normal stresses higher than 200 kPa, the mixtures presented a friction angle equal to the matrix of sandy soil used.